The Molecular Basis and Therapeutic Potential of Let-7 MicroRNAs against Colorectal Cancer - Rei Mizuno; Kenji Kawada; Yoshiharu Sakai (Canadian Journal of Gastroenterology and Hepatology)
Although a number of studies have revealed the underlying mechanisms which regulate the development of colorectal cancer (CRC), we have not completely overcome this disease yet. Accumulating evidence has shown that the posttranscriptional regulation by the noncoding RNAs such as microRNAs plays an important role in the development or progression of CRC. Among a number of microRNAs, the let-7 microRNA family that was first discovered in C. elegans and conserved from worms to humans has been linked with the development of many types of cancers including CRC. The expression level of let-7 microRNAs is temporally low during the normal developmental processes, while elevated in the differentiated tissues. The let-7 microRNAs regulate the cell proliferation, cell cycle, apoptosis, metabolism, and stemness. In CRC, expressions of let-7 microRNAs have been reported to be reduced, and so let-7 microRNAs are considered to be a tumor suppressor. In this review, we discuss the mechanisms regulating the let-7 microRNA expression and the downstream targets of let-7 in the context of intestinal tumorigenesis. The application of let-7 mimics is also highlighted as a novel therapeutic agent.